Generalized and numerical solution for a quasilinear parabolic equation with nonlocal conditions - KANCA, Fatma; BAGLAN, Irem (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
In this paper we study the one dimensional mixed problem with non- local boundary conditions, for the quasilinear parabolic equation. We prove an existence, uniqueness of the weak generalized solution and also continuous depen- dence upon the data of the solution are shown by using the generalized Fourier method. We construct an iteration algorithm for the numerical solution of this problem. We analyze computationally convergence of the iteration algorithm, as well as on test example. Mathematics Subject Classification (2010): 35K55.